(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
Sulfanilamides are synthetic antimicrobial agents that inhibit the growth of bacteria. Antituberculosis agents are a group of potent drugs that kill mycobacteria, while antiviral agents prevent viruses from entering or multiplying in cells. These drugs inhibit the growth and reproduction of bacteria (bacteriostatic effect). They work by disrupting the synthesis of folic acid by microbes. Tuberculosis (tuberculosis) is a complex and longterm disease, usually requiring the use of several drugs in combination. Sulfanilamide drugs are a group of antibacterial chemotherapeutic agents and are important in the treatment of infectious diseases. This article provides a scientific analysis of the pharmacological properties, mechanism of action, pharmacokinetics, and clinical application of sulfanilamide drugs. Sulfanilamides disrupt the synthesis of folic acid in microorganisms through competitive antagonism with paraaminobenzoic acid, and as a result, they inhibit the growth and reproduction of bacteria. The results of the study indicate the importance of sulfonamides in pharmaceutical and clinical practice